Multimedia and Communications Technology, 2nd Edition - Heath, Steve (Routledge, 1999)
Multimedia and Communications Technology is a practical explanation of the technologies that bring together existing products such as the PC, telephone and television. It is precisely this revolution that the book addresses - offering an up to date technical overview of developments in PC technology, video and audio compression, telecommunications and many other disciplines. Written as a series of tutorials, the book starts with the fundamental techniques of digital audio and video, moving on to compression techniques such as JPEG and MPEG. The delivery systems for multimedia are then covered, starting with the CD and on to telephones, local and wide area networks and ATM and ASDL. The final chapters describe how these technologies are brought together in some key applications: · video conferencing · digital video broadcasting · video on demand · interactive television Steve Heath is responsible for European Strategy and Technology Development at Motorola. He has had many years experience in computer design and has presented papers on multimedia technology at international conferences. He is a well known technical writer and has written fourteen other books for Focal Press, Newnes and Butterworth-Heinemann.